PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS WEBSITE UNTUK MENINGKATKAN LITERASI DIGITAL SISWA SMP - Rosita, Dewi; Isnaynun, Isnaynun; Andrea, Reza; Pratama, Angga (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
The limited use of engaging and interactive learning media during the learning process, particularly in the subject of informatics at junior high schools, has reduced students' interest in learning. One application of technology in the field of education is the development of a website as an e-learning medium. This study aims to determine the feasibility level of website-based learning media and analyze the level of digital literacy among junior high school students. This research is a development study (R&D) using the Brog and Gall model, which includes the stages of needs analysis, planning, initial product development, validation, testing, first product revision, second product revision, effectiveness testing, and dissemination. The results of the study from material expert validation showed a score of 4.7 in the